Unveiling the Venom Composition of the Colombian Coral Snakes Micrurus helleri, M. medemi, and M. sangilensis - Rodríguez-Vargas, Ariadna; Franco-Vásquez, Adrián Marcelo; Bolívar-Barbosa, Janeth Alejandra; Vega, Nohora; Reyes-Montaño, Edgar; Arreguín-Espinosa, Roberto; Carbajal-Saucedo, Alejandro; Angarita-Sierra, Teddy; Ruiz-Gómez, Francisco (Toxins, 2023)
Little is known of the biochemical composition and functional features of the venoms of poorly known Colombian coral snakes. Here, we provide a preliminary characterization of the venom of two Colombian endemic coral snake species, Micrurus medemi and M. sangilensis, as well as Colombian populations of M. helleri. Electrophoresis and RP-HPLC techniques were used to identify venom components, and assays were conducted to detect enzyme activities, including phospholipase A2, hyaluronidase, and protease activities. The median lethal dose was determined using murine models. Cytotoxic activities in primary cultures from hippocampal neurons and cancer cell lines were evaluated. The venom profiles revealed similarities in electrophoretic separation among proteins under 20 kDa. The differences in chromatographic profiles were significant, mainly between the fractions containing medium-/large-sized and hydrophobic proteins; this was corroborated by a proteomic analysis which showed the expected composition of neurotoxins from the PLA2 (~38%) and 3FTx (~17%) families; however, a considerable quantity of metalloproteinases (~12%) was detected. PLA2 activity and protease activity were higher in M. helleri venom according to qualitative and quantitative assays. M. medemi venom had the highest lethality. All venoms decreased cell viability when tested on tumoral cell cultures, and M. helleri venom had the highest activity in neuronal primary culture. These preliminary studies shed light on the venoms of understudied coral snakes and broaden the range of sources that could be used for subsequent investigations of components with applications to specific diseases. Our findings also have implications for the clinical manifestations of snake envenoming and improvements in its medical management.